Analisis Produktivitas Pembuatan Kerupuk Guna Meningkatkan Produksi Menggunakan Metode OMAX dan FTA - Muhammad Gilbran Bintang Saputra; Erni Puspanantasari Putri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the productivity level of the production process at UD Kerupuk Mawar and identify the factors causing low productivity. The problems faced by the company include imbalance between input and output, high defect rates, raw material waste, inefficient production time, and machine downtime. The methods used in this study are Objective Matrix (OMAX) to measure productivity based on several criteria and Fault Tree Analysis (FTA) to identify the root causes of the problems. The research data were collected from six months of production activities, including raw materials, labor, production time, machine downtime, defective products, and production output. The results showed that production productivity fluctuated and had not reached the optimal target. The main factors affecting productivity decline were high defect rates, machine downtime, and inefficient production time. Improvement proposals include increasing production supervision, regular machine maintenance, and improving work methods.